Analysis of Eighth-Grade Students’ Critical and Creative Thinking Skills In Solving Open-Ended Mathematics Problems - Rifiyani; Kho, Ronaldo; Hutabarat, Ida Maryati (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
Mathematics plays a crucial role in fostering students’ logical and higher-order thinking skills, yet many Indonesian students still struggle with problem-solving, particularly in applying mathematical concepts to financial literacy contexts. This study aims to analyze the critical and creative thinking abilities of eighth-grade students at SMP Al-Ihsan Kotaraja in solving open-ended mathematical problems. A descriptive qualitative approach was employed, with participants categorized into high, moderate, and low academic achievement levels. Data were collected through open-ended problem-solving tests, interviews, and classroom observations, and analyzed using rubrics for critical and creative thinking. The findings reveal that high-achieving students reached maximum scores across indicators of critical and creative thinking, demonstrating strong reasoning, reflection, and originality in solutions. Conversely, students with moderate and low achievement levels experienced difficulties in constructing valid inferences, generating diverse strategies, and elaborating on problem-solving processes. These results highlight the effectiveness of open-ended problems as diagnostic and instructional tools for developing higher-order thinking skills. The study underscores the importance of differentiated instruction to address students’ varying abilities and suggests that the integration of the Problem-Based Learning model can enhance mathematical problem-solving skills while strengthening financial literacy.